2021
DOI: 10.1111/tbed.14103
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiological insights into Trypanosoma vivax in Argentina: From the endemic Gran Chaco to outbreaks in the Pampas

Abstract: Argentina is a home to millions of beef and dairy cattle and is one of the world's major exporters of meat. In the present study, Trypanosoma vivax was prevalent (2016–2018) in two major livestock farming regions, the Gran Chaco and the Pampas. In the Gran Chaco, 29% and 51% of animals (n = 72, taurine x zebuine crossbreed) were, respectively, positive by TviCATL‐PCR and the more sensitive fluorescent fragment length barcoding (FFLB) method. While 18.4/38.8% of breeding cows (n = 49) tested positive by PCR/FFL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 48 publications
(158 reference statements)
3
17
0
Order By: Relevance
“…, however, to date Buenos Aires has no cases of T. vivax, so the assessment in the provinces of Cordoba and Santa Fe covers almost 70% of the dairy basin, where T. vivax is endemic(17).Our results are comparable to those of other studies in South America, highlighting the high prevalence of this disease in endemic regions. An epidemiological study in the Pantanal region of Brazil using indirect ELISA reported an average seroprevalence rate of 56%(41).…”
supporting
confidence: 79%
See 3 more Smart Citations
“…, however, to date Buenos Aires has no cases of T. vivax, so the assessment in the provinces of Cordoba and Santa Fe covers almost 70% of the dairy basin, where T. vivax is endemic(17).Our results are comparable to those of other studies in South America, highlighting the high prevalence of this disease in endemic regions. An epidemiological study in the Pantanal region of Brazil using indirect ELISA reported an average seroprevalence rate of 56%(41).…”
supporting
confidence: 79%
“…Significant economic impacts have been caused by losses in dairy cattle infected with T. vivax , leading to the treatment of entire herds and resulting in a substantial reduction in milk production from affected herds (17,48). In this study, we demonstrated high seroprevalence of the disease in an affected region, suggesting a possible spread of the disease in the southern and eastern areas of the Pampas region, as observed by other authors (17,51).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…AT is considered a major constraint on agricultural production in Sub-Saharan Africa; it is estimated to infect over 70 million cattle annually and is responsible for production losses that total billions of dollars per year ( 2 , 3 ). T. vivax is a cause of concern in Central and South America where its geographical distribution has grown in recent years ( 4 6 ). Current estimates indicate that over 11 million cattle are at risk of infection in the extensive cattle ranching areas of the Brazilian Pantanal and Bolivian lowlands alone ( 5 ).…”
Section: Introductionmentioning
confidence: 99%